Integrated hydrological modeling of the North China Plain: Options for sustainable groundwater use in the alluvial plain of Mt. Taihang - Shu, Yunqiao; Villholth, Karen G.; Jensen, Karsten H.; Stisen, Simon; Lei, Yuping (Journal of hydrology (Amsterdam), 2012)
► The hydrological model MIKE SHE was applied to a part of the North China Plain. ► Groundwater tables are declining due to intensive use of groundwater for irrigation. ► A scenario analysis demonstrated the effect of different management actions. ► Region-wide crop and irrigation system changes may stabilize groundwater levels. ► Highest impact from deficit irrigation, wastewater irrigation, and alternating winter fallow. The integrated hydrological model MIKE SHE was applied to a part of the North China Plain to examine the dynamics of the hydrological system and to assess water management options to restore depleted groundwater resources. The model simulates the spatio-temporal distribution of recharge to and the associated dynamics of the alluvial aquifers based on climatic conditions, land use, soil characteristics, irrigation and coupled unsaturated-saturated zone processes. The model was auto-calibrated for the period 1996–2002 against daily observations of groundwater head from wells distributed across the 7230km2 region and actual evapotranspiration measured at an agricultural station located within the model area. The model simulations compared well with observations and acceptable values were obtained for both root mean square error and correlation coefficient. The calibrated model was subsequently used for scenario analysis of the effect of different cropping rotations, irrigation intensity, and other water management options, like the implementation of the South to North Water Transfer (SNWT) project. The model analysis verified that groundwater tables in the region are subject to steep declines (up to 1m/yr) due to decades of intensive exploitation of the groundwater resources for crop irrigation, primarily the widespread crop rotation of irrigated winter wheat and mostly rainfed summer maize. The SNWT project mitigates water stress in Shijiazhuang city and areas adjacent to wastewater canals but cannot solely reverse declining water tables across the region. Combining the SNWT project and implementing region-wide crop and irrigation system changes, including deficit irrigation, wastewater irrigation, and alternating winter fallow, provides a feasible means to stabilize groundwater levels in the area.